Growth suppression activity of bradykinin antagonists in glioma cells - Avdieiev, S.S.; Gera, L.; Hodges, R.; Vassetzky, Y.S.; Kavsan, V.M. (Вiopolymers and Cell, 2014)
The present study was Aimed at analyzing the effect of bradykinin (BK) antagonists on proliferation of the human glioblastoma cells U373. Methods. MTT-based cell proliferation assay. Results. BKM-570 revealed a significant antiproliferative activity in the U373 cells with LC50 3,8 M. Conclusions. The antiproliferative properties of BK antagonists were shown in vitro using the glioma cells. Further investigations of the molecular mechanisms of their action and pre-clinical studies on animal models are needed for the evaluation of these compounds as new anti-cancer drugs. Мета цього дослідження полягала в аналізі впливу антагоністів брадикініну на проліферацію клітин гліобластоми людини U373. Методи. МТТ аналіз пролиіферації клітин. Результати. BKM-570 продемонстрував значну антипроліферативну активність у клітинах U373 (LC50 3,8 мкМ). Висновки. Антипроліферативні властивості антагоністів брадикініну показано з використанням моделі гліоми in vitro. Подальші дослідження молекулярних механізмів дії, а також доклінічні випробування із застосуванням тваринних моделей необхідні для оцінювання зазначених сполук як нових протиракових препаратів. Цель данного исследования состояла в анализе влияния антагонистов брадикинина на пролиферацию клеток глиобластомы человека U373. Методы. МТТ анализ пролиферации клеток. Результаты. BKM-570 продемонстрировал значительную антипролиферативную активность в клетках U373 (LC50 3,8 мкМ). Выводы. Антипролиферативные свойства антагонистов брадикинина показаны с использованием модели глиомы in vitro. Дальнейшие исследования молекулярных механизмов действия, а также доклинические испытания с применением животных моделей необходимы для оценки этих соединений в качестве новых противораковых препаратов.